2012
DOI: 10.1073/pnas.1212545109
|View full text |Cite
|
Sign up to set email alerts
|

An image-based screen identifies a small molecule regulator of megakaryopoiesis

Abstract: Molecules that control the lineage commitment of hematopoietic stem cells (HSCs) may allow the expansion of enriched progenitor populations for both research and therapeutic uses. In an effort to better understand and control the differentiation of HSCs to megakaryocytes, we carried out an image-based screen of a library of 50,000 heterocycles using primary human CD34 + cells. A class of naphthyridinone derivatives was identified that induces the differentiation of common myeloid progen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…[51][52][53][54] Small molecules acting through platelet-derived growth factor receptors or the TPO receptor MPL have been identified as able to induce ex vivo production of MKs and platelets. [55][56][57][58] Our work describes a novel strategy to enhance in vitro MK generation, based on insights from the integrated analysis of a human iPSC model of a monogenic human disease. Our study demonstrated that isogenic iPSC pairs, with or without a specific mutation, not only recapitulate precisely the disease phenotypes but also help discover new druggable targets distinct from the original mutated gene.…”
Section: Discussionmentioning
confidence: 99%
“…[51][52][53][54] Small molecules acting through platelet-derived growth factor receptors or the TPO receptor MPL have been identified as able to induce ex vivo production of MKs and platelets. [55][56][57][58] Our work describes a novel strategy to enhance in vitro MK generation, based on insights from the integrated analysis of a human iPSC model of a monogenic human disease. Our study demonstrated that isogenic iPSC pairs, with or without a specific mutation, not only recapitulate precisely the disease phenotypes but also help discover new druggable targets distinct from the original mutated gene.…”
Section: Discussionmentioning
confidence: 99%
“…Because LOX amplifies PDGF receptor signaling, and because inhibition of this signaling is important for transition of common myeloid progenitors to megakaryocytes, 46 LOX inhibition may be helpful in halting megakaryocyte proliferation in MPNs. Yet, we do not rule out the possibility that LOX influences the MKP pool also via mechanisms independent of PDGF, such as its newly identified influence on collagen receptors.…”
Section: Org Frommentioning
confidence: 99%
“…UCB‐derived CD34 cells were expanded in combination with reagents previously reported to increase CD34 cell expansion, as well as on a pseudo‐3D membrane. The aryl hydrocarbon signaling inhibitor SR1, copper chelator TEPA, and caspase inhibitor zVADfmk have been shown to increase the CD34‐fold expansion in vitro. We found that the use of the aryl hydrocarbon receptor inhibitor (SR1) increased the CD34‐fold expansion to a mean of 85‐fold on Day 7 (Fig.…”
Section: Resultsmentioning
confidence: 99%